Effect of mentoplasty on esthetic perception of dental surgeons, dental students and lay persons - Pithon, Matheus; Guedes, Diego Oliveira; Leal, Solane; Silva, Maria Luiza; Dantas, Raphaela; Pelegrini, Ketly; Coqueiro, Raildo da Silva (Brazilian Dental Science, 2019)
Objective: awas to evaluate the influence of mentoplasty on esthetic perception of dental surgeons, dental students and lay persons. In addition, to determine whether the outstanding chin affects the perceived desire for orthognathic surgery. Material and Methods: An image of an ideal silhouette was created. This image was manipulated to create another six images with different degrees of retrogenia and progenia in increments, advancing and receding the chin on a scale of 5 mm (from +15 to -15 mm) in the anteroposterior and vertical directions. Once the images were obtained, a questionnaire was created, which was evaluated by lay persons, dental surgeons and dental students (n = 50). The evaluators used a visual analog scale to analyze the images, establishing a score ranging from 0 to 10. Associated with the scale, the evaluators were asked whether they wished to have some surgical correction performed if the image in question were a representation of their own facial profile. Results: demonstrated that image H (0 mm) was ranked as the most attractive by the dental surgeons, while the dental students and lay persons scored B (-5 mm) as the best image. In general, images A (+15 mm) and D (-15 mm) were those that most induced a desire for corrective surgery. Conclusion: the prognathic and retrognathic facial profiles were unpleasant and perceptible to the dentist, dental student and lay person. The more projected and retracted the chin was, the greater was the desire to have orthognathic surgery performed. Keywords Esthetics; Mentoplasty; Face.